2009
DOI: 10.1007/978-3-642-04076-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Target Acquisition with Force Feedback: The Effect of Different Forces on the User’s Performance

Abstract: Besides realistic haptic rendering of objects, haptic feedback can also be used to provide an abstract feedback channel. This can either be realised by a tactile or a force feedback stimulus. When using forces, care has to be taken that the user's performance is not influenced in a negative way. However, as it is not obvious to determine a suitable force, and currently not many guidelines exist. Therefore, in this paper we investigate the influence on some important parameters that define a force (shape, durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Post hoc comparisons for FI showed that above a certain force integral value (FI = 85.94) the trial completion time deteriorated significantly (p < .01). This value, 85.94, is somewhat higher than in our previous experiments [3].…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…Post hoc comparisons for FI showed that above a certain force integral value (FI = 85.94) the trial completion time deteriorated significantly (p < .01). This value, 85.94, is somewhat higher than in our previous experiments [3].…”
Section: Resultscontrasting
confidence: 59%
“…It can be assumed that the majority of the performance penalty is caused by the interruption of the ballistic movement. In our previous work [3] more graphs are available motivating this statement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations